Eyeing the red storm Eisenhower and the first attempt to build a spy satellite - Dienesch, Robert M. (University of Nebraska Press, 2016)
In 1954 the U.S. Air Force launched an ambitious program known as WS-117L to develop the world's first reconnaissance satellite. The goal was to take photographic images from space and relay them back to Earth via radio. As a fiscal conservative, Eisenhower believed a strong economy was the key to surviving the Cold War and saw satellite reconnaissance as a means to understand the Soviet military challenge more clearly and thus keep American defense spending under control.